ANALISIS MISKONSEPSI SISWA PADA MATERI GELOMBANG DENGAN METODE THREE-TIER MULTIPLE CHOICE DI SMPN 1 KEJAYAN - Agung Suci Dian Sari; Ruslimin. A; Neliatul Maksudah; Valina Attamaamah; Nuning Maslukha (LPPM Universitas Cipta Mandiri, 2026)
Physics in class IX junior high school that has the potential to cause learning difficulties is the material on waves. This topic includes the definition of waves, their various types, and wave parameters such as wavelength, frequency, period, amplitude, and wave propagation velocity. These concepts are abstract and often cannot be seen directly, so students are more likely to build understanding based on everyday experiences and pre-existing knowledge. The initial concepts formed are often incompatible with scientific concepts accepted by experts. Inaccurate understanding from the beginning that contradicts scientific theory is known as misconceptions. Therefore, this study aims to analyze students' misconceptions on wave material using the Three-Tier Multiple Choice method at SMPN 1 Kejayan with 30 students in class XI A. The method used is quantitative descriptive with the research instrument in the form of a diagnostic test sheet for misconceptions on wave material using the three-tier multiple choice method with a total of 10 questions. The data collection procedure includes the planning and implementation. The data analysis is based on the CRI score and the Three-Tier Multiple Choice answer criteria in the percentage recapitulation. Based on the research results, 57% of students had misconceptions about wave material.